Politics, Participation and Big Data. Introductory Reflections on the Ontological, Epistemological, and Methodological Aspects of a Complex Relationship - Alice Mattoni (Coordinamento SIBA, 2018)
This editorial defines big data as an inherently political object and then briefly discusses its ontological, epistemological, and methodological implications in the social sciences. Furthermore, it addresses these issues in connections with the realm of politics, political participation and political mobilization. Finally, it addresses three main emergent themes related to big data in the broad realm of politics. First, big data as a methodological conundrum - something that can possibly empower or completely bias research activities and results. Second, big data as an object of study in its own right, a contested research and political terrain characterized by strong power dynamics between private and public actors and entwining with governance processes at all levels - from the national to the transnational one. Third, big data as research catalyser that can leverage our understanding of participation and contentious dynamics.